PERSPECTIVES OF TIGECYCLINE TREATMENT OF SURGICAL SITE INFECTIONS IN ONCOLOGIC PATIENTS - S. D. Mitrokhin; A. A. Sokolov (Антибиотики и Химиотерапия, 2020)
Criteria of tigecycline (Tygacil) use for the treatment surgical infections in oncologic in patients were developed. High efficacy of tigecycline in vitro and in vivo against multiresistant hospital strains persistent in the surgical department of the gastrointestinal oncologic division.